The Perspectives of Legal System on the Policy of Unifying Fuel Pricing in Indonesia - Sihombing, B.F. (International Journal of Energy Economics and Policy, 2018)
This study aims to find out about the perspectives of legal system on the policy of unifying fuel pricing in Indonesia. Various problems of fuel in Indonesia such as legal issues, pricing and ensuring the supply, availability and smooth supply to the public in the domestic market, the government is obliged to intervene in determining the fuel price and at the same time guarantee its availability in the domestic market. this study researchers use normative juridical research methods, research on the legal principles contained in regulations and legislation using qualitative data. From the results of the discussion, it was concluded that the government policy regarding the establishment of fuel price unification in Indonesia is an effective economic law policy in order to realize the development, prosperity and prosperity of the Indonesian people as stipulated in the Preamble of the 1945 Constitution and 1945 Constitution article 33 as its legal basis. Keywords: law system, unification of fuel pricing, preamble of the 1945 Constitution, article 33 of the 1945 Constitution JEL Classifications: K23, K32, Q48 DOI: https://doi.org/10.32479/ijeep.7049